Teatro - educação: uma vivência artística e didática na brinquedoteca da EAUFPA - MELO, Faye Cristina Celeiro (2023)
The present work intends to describe an artistic and didactic experience developed at the application school of the Federal University of Pará - UFPA, in Belém / PA, in the year 2017, during the supervised internship (Teaching Practice of Theater I, of the Degree in Theater of ETDUFPA), in the playroom, a space where playful and pedagogical elements can be found to attend the PRE I and PRE II classes of early childhood education (children aged 4 to 5 years), in the morning shift. The room became the stage for presentations: theater, folklore legends from Pará, handicrafts, literature, music, dance and toys. In the space where the activities were carried out, new ways of learning from the daily school life were discovered, as they were used as resources: text clipping, theatrical staging, costumes and the text of the statute of the child and adolescent - ECA. As a result, the effective participation of children who learned about folklore legends along with art. 4th from ECA, showing interest and curiosity, where they made constant inquiries about their rights and the characters of the didactic experience. Thus, we realize that the playful elements of interaction existing in the space, together with the various toys, contribute to the social and cultural formation of children.